Beclomethasone aerosol in childhood asthma - Godfrey, S. (1973)
Twenty children have been treated with the steroid aerosol beclomethasone, half of them in an open trial and the other half in a controlled cross-over trial. Children were assessed by means of clinical examination, diary records, and twice-daily peak flow rate measurements made at home. After 1 to 2 months all but 1 of the 16 children who were initially taking systemic steroids or corticotrophin were weaned off these drugs. The cross-over trial showed a significant improvement on the active drug, in terms of diary score, bronchodilator use, steroid dose, and twice-daily peak expiratory flow measurements. Adrenal function was entirely normal after 1 and 3 months on the drug as measured by morning cortisol levels and the response to tetracosactrin. There were no side effects, apart from the reappearance of hay fever or eczema in some children previously on systemic steroids. Follow-up for a mean of 4·5 ± 2·2 (SD) months showed the continuing efficacy of beclomethasone, though an increase in dose has been needed in some children. The advantages of aerosol steroid therapy in children are noted.